ChemInform Abstract: Stereochemical Determination of the Leupyrrins and Total Synthesis of Leupyrrin A1. Issue 35 (September 2015) - Herkommer, Daniel; Thiede, Sebastian; Wosniok, Paul R.; Dreisigacker, Sandra; Tian, Maoqun; Debnar, Thomas; Irschik, Herbert; Menche, Dirk
Abstract The relative and absolute configurations of potent antifungal agents leupyrrin A1 (I) and B1 (II) are determined by a combination of high field NMR studies, molecular modeling, and chemical derivatization.